Preface and biographic notes for the special issue on graphics for serious games - Debattista, Kurt (2010)
The use of serious games and applications has emerged as a dominating force in training, education and simulation due to the focus on creating compelling interactive environments at reduced costs by adopting its capacity of engaging younger hi-tech generations in the highly motivated gaming environments and to the opportunities offered by the commodity technologies commonly associated with the entertainment industries. This field is informed by theories, methods, applications and the state-of-the-art in a number of areas based on technological principles and innovation, advances in games design, pedagogic methodologies and the convergence of these fields. This special issue presents a highlight of this diverse community and demonstrates how computer graphics is contributing and being enhanced by seriousgames. The four papers chosen for this special issue offer a new contribution to the world of graphics, in terms of new tools or adapting more traditional graphic methods for the use in training applications. “A Head Movement Propensity Model for Animating Gaze Shifts and Blinks of Virtual Characters” by Peters and Qureshi is an extended version of the second IEEE Conference on Games and Virtual Worlds for Serious Applications (VS-Games 2010) best paper. It outlines how to animate more believable in-game characters, modelling the behaviour of gaze shifts and blinks following the characters’ attention, resulting in further user engagement with the virtual character, thus affecting learning outcomes and immersion in educational environments. The Infinitex system by Hollemeersch et al., adopts the concepts of virtual memory for the use in texture memory. This significantly enhances asset creation in games by giving artists the ability to design arbitrary large textures, increasing productivity and reducing asset re-use, effectively making the gaming experience more immersive. The authors also discuss how to make this work practically within a gaming project. The two articles on RIST and VFire adopt modern graphics methods used in games to develop systems suitable for training in environments that are considered dangerous. The “RIST: Radiological Immersive Survey Training for Two Simultaneous Users” paper, by Koepnick et al., describes a system for training National Guard Civil Support Teams to respond when dealing with dangerous radioactive materials. “VFire: Immersive Wildfire Simulation and Visualization”, by Hoang et al., provides a system for training and educating firefighters and policy makers to combat wild fires, simulating the spread based on real-world data and allowing realistic visualization of the virtual scenarios; both simulation and visualization tasks are computed on a modernGPU. We hope that this special issue will contribute to foster wider interest in this exciting and emerging field, leading to the emergence of new application areas and encouraging more graphics researchers and practitioners to participate in future original contributions.